Tìm x : (x+2)(x-3) + 6 = x (x+5) 2, rút gọn A= 2x/x²+xy + 6x/x²-y² + 3/ y-x

Tìm x : (x+2)(x-3) + 6 = x (x+5)
2, rút gọn A= 2x/x²+xy + 6x/x²-y² + 3/ y-x

2 bình luận về “Tìm x : (x+2)(x-3) + 6 = x (x+5) 2, rút gọn A= 2x/x²+xy + 6x/x²-y² + 3/ y-x”

  1. Đáp án+giải thích các bước giải:
    Gửi ạ
    (x+2)(x-3)=x(x+5)
    x^{2}-3x+2x-6=x^{2}+5x
    x^{2}-x+6-(x^{2}+5x)=0
    -6x=0
    =>x=0
    vậy x=0
    ______________________
    A= (2x)/(x^{2}+xy) + (6x)/(x^{2}-y^{2}) +3/(y-x) (đk: x \ne +-y ; x \ne 0)
    A= (2x.(x-y))/(x(x+y).(x-y)) + (6x)/((x-y)(x+y))-(3(y+x))/((y+x)(x-y))
    A= (2x-2y)/((x+y).(x-y)) + (6x)/((x-y)(x+y))-(3y+3x)/((y+x)(x-y))
    A= (2x-2y+6x-3x-3y)/((x+y)(x-y))
    A= (5x-5y)/((x+y)(x-y))
    A= (5(x-y))/((x+y)(x-y))
    A= 5/(x+y)

    Trả lời

Viết một bình luận

Câu hỏi mới